From the Journal Editor - Peace, Christopher (New Zealand Journal of Health and Safety Practice, 2024)
Haere mai! Welcome to volume 1, edition 1 of the New Zealand Journal of Health and Safety Practice! The Journal is open access and online and subscriptions are free. Although published in New Zealand we hope it will be read by workers everywhere who work in the field of health, safety and wellbeing. This edition is published at the time of International Workers' Memorial Day and the 29th anniversary of the New Zealand Cave Creek tragedy. I hope the Journal will grow to share practical, research-based knowledge that will help every worker (and visitors to workplaces) to go home physically and mentally unharmed. Much work went into the development of the Journal and I thank: the authors who spent time writing and revising the articles our anonymous reviewers who spent their time reading the submissions and making comments: you have helped set the standard for the Journal. Nik Crombie and Max Sullivan in the Victoria University of Wellington Library who helped with the backroom work and technology making the Journal free to publish. The editorial team also thanks HASANZ, Engineering New Zealand, Faculty of Asbestos Management of Australia & New Zealand, Human Factors and Ergonomics Society of New Zealand, Institute of Organisational Psychology, New Zealand Institute of Safety Management, New Zealand Occupational Health Nurses Association, New Zealand Occupational Hygiene Society, New Zealand Safety Council, AVID Plus Limited and Risk Management Ltd for financial and other support to help establish the Journal. Terje Aven, a Norwegian academic, wrote that “safety science is multidisciplinary. Its contributors and its audience range from psychologists to chemical engineers”; that safety science “covers the physics and engineering of safety; its social, policy and organisational aspects; the management of risks; the effectiveness of control techniques for safety; standardization, legislation, inspection, insurance, costing aspects, human behaviour and safety and the like.” The founding organisations of NZJHSP are similarly drawn from those disciplines. A call for papers for the July 2024 edition will go out shortly. I look forward to submissions for future editions of this Journal those focused on the practice of workplace health and safety through implementing the broad subject area of safety science to help protect workers and others and achieve good work conditions. References Aven, T. (2014). What is safety science? Safety Science, 67, 15-20. https://doi.org/10.1016/j.ssci.2013.07.026